Synnøve des Bouvries karriere ved UiT, 1972–2014: Intervju og bibliografi - Aspaas, Per Pippin (Nordlit, 2014)
The career of Synnøve des Bouvrie at the University of Tromsø, 1972–2014: Interview and bibliography. Synnøve des Bouvrie was born in Bussum near Amsterdam on 16 November 1944 as the child of a Norwegian mother and a Dutch father. After studies of classical philology at Leiden, she became one of the first lecturers at the University of Tromsø (UiT) in September 1972. A true pioneer, she has fought relentlessly for gender equality and the preservation of the so-called «small» languages at the UiT. Mastering ten languages altogether, Synnøve’s own research has always been internationally oriented. Applying an anthropological perspective on the ancient societies, she has also studied the current study of ancient tragedies from a similar, detached perspective, by means of which she has been able to single out national trends and historical contingency in cutting-edge research. Moreover, this «rare bird in Ultima Thule» is a staunch advocate for the active use of Latin in teaching and research and a prominent member of the Academia Latinitati Fovendae. In Tromsø too, she has been active in another academy, the cross-disciplinary Academia Borealis, of which she is the serving president. Moreover, she has taught and helped establish courses in various subjects outside her field of specialty at the UiT, like a cross-disciplinary course on Graeco-Roman art, archaeology, literature and history (Antikkens kultur) and comparative literature (Allmenn litteratur). The interview is highly personal, crammed with anecdotes from Synnøve’s private life and deliberations on how her upbringing may have influenced her choices as an academic. The bibliography lists her publications from 1972 to the present. In the interview she reveals that a monograph on Euripides can be expected to be published soon with an international publisher. In the appendix several illustrations are included, with captions in English.